Calibración del módulo de las tendencias del ensamblaje de fondo direccional en tres diferentes tipos de pozo para el Campo Castilla (2016)
In this paper, the geological description and history of production del Campo Castilla operated by Ecopetrol S.A. is presented; Likewise, the need to implement a software that allows to know the trend more in line assembly line, depending on the characteristics of the formation, for directional drilling is exposed. Currently, studies are underway in a number of wells drilled in order to obtain a broader database and that the error rate is decreasing.